Influence Of Exercise Nine Balls to Gawang on The Ability of The Athlete SSB Duri Galaxy U12 - Jeremia Radovan Gultom (Pusat Pengembangan Olahraga Universitas Pahlawan, 2026)
The problem in this study is that there is a lack of shooting ability of Athlete SSB Duri Galaxy U12, this can be seen from various trials and official matches and this is one of the factors causing the defeat. This type of research is a kind of weak research experiment to see the effect of the form of training. The purpose of this study is to see the effect of training in kicking nine balls towards the shooting ability of the Athlete SSB Duri Galaxy U12. The populations in this study were all active members in Athlete SSB Duri Galaxy U12 totaling 14 people. The sampling technique is by using probability sampling, where the number of samples to be taken is 14 people. Data collection techniques obtained from the pre-test and post test. The instrument in this study used the Test of shooting the ball to the target or shooting as a tool to measure shooting ability. The analysis was carried out using the t- test. Based on data analysis and discussion, it can be concluded that there is a significant effect of training kicking nine balls on goal against the shooting ability of the Athlete SSB Duri Galaxy U12.